Biblical Narratives in INTERSTELLAR (US/GB 2014) - Nir, Bina (Journal for religion, film and media, 2020)
The present paper examines the presence of biblical narratives and myths in contemporary cultural productions based on an analysis of the science fiction film Interstellar (Christopher Nolan, US 2014). Interstellar follows the space voyage of a team of experts sent through a wormhole to search for a planet fit for human settlement since Earth is in the grips of ecological catastrophe that threatens to wipe out humanity. A narrative analysis of the film reveals that it also draws much of its inspiration from Judeo-Christian sources, particularly the narratives of the Old Testament. As a work of science fiction, Interstellar relies on the work of the physicist Kip Thorne, however, in addition to its scientific subject matter, the film is also replete with biblical narratives such as the apocalypse, Noah’s ark, the tale of the spies, prophecy and the tasking of the “chosen” one with a mission, signs and miracles, the ability to control nature and to create elements within it, the idea of punishment in the form of being denied entrance to the promised land, and so on.